Effect Of Light Level On Growth And Shoot Development Of Five Species Of Tropical Saplings. - Tong, Pei Sin (2006)
Saplings of Acacia mangium, Shorea roxburghii, Dyera costulata, Eusideroxylon zwageri and Cinnamomum iners were grown at 4%, 7%, 25%, 50% and 100% relative light intensities (RLIs) and their growth was monitored by rate of increment of height and diameter, rate of production of new leaves and leaf life span. Leaves were analysed for their content of nitrogen (N), phosphorus (P), potassium (K), magnesium (Mg), calcium (Ca), chlorine (Cl), sulphur (S), boron (B), manganese (Mn), copper (Cu) and zinc ( Zn). For each RLI, two samples of leaves were taken for analysis: young fully expanded leaves and old about-to-shed leaves. From these analyses, the fate of nutrients was determined. Acacia mangium and Cinnamomum iners were found to grow best at 100% RLI, Shorea roxburghii at 50% RLI and, Dyera costulata and Eusideroxylon zwageri at 25% RLI. Acacia mangium at 100% RLI had the highest weekly height and diameter increment of 16.15 cm and 0.77 cm respectively. This is 4 times higher than the second best growth species, Shorea roxburghii at 50% RLI and 21 times higher than the slowest growth species, Eusideroxylon zwageri at 25% RLI. Acacia mangium at 100% RLI had the highest mean leaf production rate per week on leaders and branches, of 1.70 and 1.60 leaves respectively. This is 3 times higher than the second best species, Shorea roxburghii at 50% RLI and 17 times higher than the slowest growing species, Eusideroxylon zwageri at 25% RLI. At 100% RLI, Acacia mangium had the shortest average leaf life span, of 130 days on leaders and 124 days on branches. In general, average leaf life span increased with reduction in RLI for all species. A fast-growing plant is associated with higher height increment, higher diameter increment, higher mean leaf production and shorter leaf life span. The level of NPK for these species in this study shared a similar range with major agricultural crops in Malaysia. The highest rate of NPK incorporation (g per week) was found in Acacia mangium, followed by Dyera costulata, and it was relatively low for other species. The levels of NPK were higher in young leaves than the old leaves for all species at all RLIs. Dyera costulata seems to withdraw more than 60% of NPK and Shorea roxburghii more than 60% of P from old leaves before they shed. All species did not withdraw Mn and Zn.